1999
DOI: 10.1002/(sici)1097-024x(199909)29:11<1005::aid-spe270>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A code compression system based on pipelined interpreters

Abstract: This paper describes a system for compressed code generation. The code of applications is partioned into time-critical and non-time-critical code. Critical code is compiled to native code, and non-critical code is compiled to a very dense virtual instruction set which is executed on a highly optimized interpreter. The system employs dictionary-based compression by means of superinstructions which correspond to patterns of frequently used base instructions. The code compression system is designed for the Philip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…J Hoogerbrugge and L Augusteijn [17], [18] have proposed that software pipelining interpreters is a way to reduce dispatch branch cost on architectures with split indirect branches. In addition, Subroutine threading [19] has also been proposed to avoid the overheads of indirect branches in intrepreter implementations.…”
Section: Related Workmentioning
confidence: 99%
“…J Hoogerbrugge and L Augusteijn [17], [18] have proposed that software pipelining interpreters is a way to reduce dispatch branch cost on architectures with split indirect branches. In addition, Subroutine threading [19] has also been proposed to avoid the overheads of indirect branches in intrepreter implementations.…”
Section: Related Workmentioning
confidence: 99%
“…Ertl and Gregg [7] showed that interpreters (especially those using switch dispatch) spend most of their time in branch mispredictions on modern desktop architectures. Interpreter software pipelining [14] is a valuable technique for architectures with delayed branches (e.g. Philips Trimedia) or prepare to branch instructions (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Some researchers [12,24,9] have shown the virtues of reducing code size, without decompression before execution, by using bytecode interpreters tailored for one program. Compression of the bytecode, capable of direct execution without decompression, would further reduce code size.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, a virtual machine tailored for the program can be used to reduce space. This is the approach taken in [12,24,9]. Further code size reduction can be obtained with a compression of the virtual instructions.…”
Section: Introductionmentioning
confidence: 99%